Membranoproliferative glomerulonephritis in a carcinoma with unknown primary: An autopsy study - Gupta Kirti (Indian Journal of Pathology and Microbiology, 2008)
Kidney disease frequently complicates malignancy and its treatment. Although many solid and hematologic cancers may involve the renal parenchyma, clinical sequelae are usually not prominent. Published reports cite membranous nephropathy as the most common malignancy-associated glomerulopathy, occurring with many carcinomas and occasionally with leukemia and lymphoma followed by minimal change disease. Rarely membranoproliferative glomerulonephritis (MPGN) has been reported in patients with malignancy. The mechanism by which malignancy induces disease remains unproved, but may involve deposition of tumor antigen in the subepithelial space with in situ immune complex formation and subsequent complement activation. Treatment of the underlying malignancy may lead to resolution of nephrotic syndrome, lending indirect support to this theory. We report a rare autopsy case of a patient with metastatic carcinoma (with unknown primary) associated with MPGN. The association between MPGN and metastatic carcinoma with unknown primary is uncommon and has not been previously reported in the literature.